Increased serum level of IL-6 predicts poor prognosis in anti-MDA5-positive dermatomyositis with rapidly progressive interstitial lung disease - Yuanyuan Niu; Suling Liu; Qian Qiu; Di Fu; Youjun Xiao; Liuqin Liang; Yang Cui; Shanhui Ye; Hanshi Xu (Arthritis Research & Therapy)
Abstract Backgroud Anti-melanoma differentiation-associated protein 5 antibody-positive dermatomyositis (anti-MDA5-positvie DM) is a subtype of dermatomyositis with a poor prognosis, characterized by rapidly progressive interstitial lung disease (RP-ILD). The study aims to investigate the significance of serum cytokines profiles and peripheral lymphocytes in predicting prognoses of anti-MDA5-positvie DM with RP-ILD. Furthermore, it seeks to analyze longitudinal data of lymphocytes during hospitalization to identify distinct trajectories and cluster patients accordingly. Methods A total of 168 patients with anti-MDA5-positive DM were enrolled in this retrospective study from two cohorts. Univariate and multivariate Cox regression analyses were conducted to determine the predictors of 6-month all-cause mortality and RP-ILD. Group-based trajectory modeling (GBTM) was employed to model the trajectories of longitudinal peripheral lymphocytes. Results In the multivariate Cox regression analysis, IL-6 ≥ 13.41pg/mL, lymphocytes < 0.5 × 109 /L, lymphocytes from 0.5 to 1.0 × 109 /L, older age, and elevated LDH were identified as independent predictors of 6-month all-cause mortality. Furthermore, IL-6 ≥ 13.41pg/mL, lymphocytes < 0.5 × 109 /L, and lymphocytes from 0.5 to 1.0 × 109 /L were found to be independent predictors of RP-ILD. Additionally, three trajectory groups of lymphocytes within the first week after admission were established based on GBTM. These groups included: Group 1, with low-level of lymphocytes that declined; Group 2, with medium-level of lymphocytes that slightly rose; and Group 3, with high-level of lymphocytes that rose. Notably, group 1 showed the highest mortality (90.7%) and all experiencing RP-ILD. Increased expression of IL-6 in lung tissues was observed in two cases with RP-ILD compared to two cases without RP-ILD. We also found the increased infiltration of CD4 + and CD8 + T cells, particularly CD8 + T cells, in lung tissues from patients with RP-ILD. Conclusions Our study demonstrated that increased level of serum IL-6 (≥ 13.41pg/mL) and severe lymphopenia were promising predictors of 6-month all-cause mortality and the occurrence of RP-ILD in anti-MDA5-positive DM patients. Furthermore, tracking distinct trajectories of lymphocytes during hospitalization can be utilized to cluster patients.